Effects of pruning and nutrition on growth and yield of hydroponic tomatoes (Lycopersicon esculentum Mill) - Fulton, Craig Mark (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScAgric)--Stellenbosch University, 2011.